Outcomes of infants born to women with influenza A(H1N1)pdm09. Issue 2 (9th January 2019) - Newsome, Kim; Alverson, C. J.; Williams, Jennifer; McIntyre, Anne F.; Fine, Anne D.; Wasserman, Cathy; Lofy, Kathryn H.; Acosta, Meileen; Louie, Janice K.; Jones‐Vessey, Kathleen; Stanfield, Valoree; Yeung, Alice; et al.
Abstract : Background: Pregnant women with influenza are more likely to have complications, but information on infant outcomes is limited. Methods: Five state/local health departments collected data on outcomes of infants born to pregnant women with 2009 H1N1 influenza reported to the Centers for Disease Control and Prevention from April to December 2009. Collaborating sites linked information on pregnant women with confirmed 2009 H1N1 influenza, many who were severely ill, to their infants' birth certificates. Collaborators also collected birth certificate data from two comparison groups that were matched with H1N1‐affected pregnancies on month of conception, sex, and county of residence. Results: 490 pregnant women with influenza, 1, 451 women without reported influenza with pregnancies in the same year, and 1, 446 pregnant women without reported influenza with prior year pregnancies were included. Women with 2009 H1N1 influenza admitted to an intensive care unit (ICU; n  = 64) were more likely to deliver preterm infants (<37 weeks), low birth weight infants, and infants with Apgar scores <=6 at 5 min than women in comparison groups (adjusted relative risk, aRR = 3.9 [2.7, 5.6], aRR = 4.6 [2.9, 7.5], and aRR = 8.7 [3.6, 21.2], for same year comparisons, respectively). Women with influenza who were not hospitalized and hospitalized women not admitted to the ICU did not have significantly elevated risks for adverse infant outcomes. Conclusions: Severely ill women with 2009 H1N1 influenza during pregnancy were more likely to have adverse birth outcomes than women without influenza, providing more support for influenza vaccination during pregnancy.